2009
DOI: 10.1074/jbc.m804334200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Targeting and Coupling of NHE1-IntegrinαIIbβ3-NCX1 by Lipid Rafts following Integrin-Ligand Interactions Trigger Ca2+ Oscillations

Abstract: The cyclic calcium release and uptake during calcium oscillation are thought to result from calcium-induced calcium release (CICR); however, it is unclear, especially in nonexcitable cells, how the initial calcium mobilization that triggers CICR occurs. We report here a novel mechanism, other than conventional calcium channels or the phopholipase C-inositol trisphosphate system, for initiating calcium oscillation downstream of integrin signaling. Upon integrin ␣ IIb ␤ 3 binding to fibrinogen ligand or the disi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
(58 reference statements)
3
24
0
Order By: Relevance
“…NHE1 accumulated in restricted patches (ϳ200 nm) in the plasma membrane, observed by confocal microscopy. We observed colocalization of NHE1 with GM1 and cosedimentation of NHE1 with flotillin-1, suggesting that a substantial portion of NHE1 is localized in lipid rafts, consistent with earlier studies (5,55). Lipid rafts are dynamic assemblies enriched in sphingolipid, cholesterol, and glycosylphosphatidylinositol (GPI)-anchored proteins, and clustered lipid rafts may serve as heterogeneous platforms that facilitate efficient signaling (32).…”
Section: Discussionsupporting
confidence: 91%
“…NHE1 accumulated in restricted patches (ϳ200 nm) in the plasma membrane, observed by confocal microscopy. We observed colocalization of NHE1 with GM1 and cosedimentation of NHE1 with flotillin-1, suggesting that a substantial portion of NHE1 is localized in lipid rafts, consistent with earlier studies (5,55). Lipid rafts are dynamic assemblies enriched in sphingolipid, cholesterol, and glycosylphosphatidylinositol (GPI)-anchored proteins, and clustered lipid rafts may serve as heterogeneous platforms that facilitate efficient signaling (32).…”
Section: Discussionsupporting
confidence: 91%
“…It is currently unknown whether the increased intracellular calcium levels are directly related to PIP 2 hydrolysis in the cell or are attributable to other mechanisms related to calcium influx. In mammalian cells, the physical interaction between ␣ II ␤ 3 integrin, sodium-proton exchangers, and sodium-calcium exchangers occurs simultaneously with integrin binding to ligand and results in increased intracellular calcium levels (56). Additionally, in phagocytes, extracellular calcium influx was shown to be essential for movement of an integrin bound to adenylate cyclase toxin from Bordetella into lipid rafts (3).…”
Section: Figmentioning
confidence: 99%
“…Previously, we demonstrated that activation of platelet and CHO ␣IIb␤3 cells (recombinant CHO cells expressing the human integrin ␣IIb␤3 protein) by fibrinogen and recombinant rhodostomin (RGD-containing protein from Agkistrodon rhodostoma snake venom), can induce cell adhesion, spreading, and intracellular calcium oscillation (10 -14). We also reported that integrin ␣IIb␤3 downstream signals induced an interaction of NHE1-integrin ␣IIb␤3 -NCX1 on intracellular vesicles then targeting to the plasma membrane, leading to the formation of functional complexes in lipid raft microdomains (15,16). NHE1 and NCX1 both appear in homodimeric forms and are functionally coupled; NHE1 drives sodium ion influx, which in turn activates NCX1 in a reverse mode to generate a calcium influx and modulate intracellular calcium oscillations (15,(17)(18)(19)(20).…”
mentioning
confidence: 93%